Exploring Syndrome Differentiation Approaches for Acupuncture Treatment of Allergic Rhinitis Based on the Principle of “Yang Transforms Qi, Yin Forms Substance” - Li, Qiang; Ji, Changchun; Guo, Jia; Ma, Hui (Journal of Contemporary Medical Practice, 2025)
Allergic rhinitis (AR) is a non-infectious inflammatory condition characterized by symptoms such as nasal itching, sneezing, watery nasal discharge, and nasal congestion. It often persists and recurs, posing challenges for effective treatment. Modern medicine primarily employs pharmacotherapy and immunotherapy, yet these treatments may cause adverse reactions. Traditional Chinese Medicine (TCM) categorizes AR under the term “Bi Qiu,” attributing its etiology to the deficiency of vital energy (Qi) in the lung, spleen, and kidney organs, which makes the body susceptible to wind-cold or abnormal qi, leading to the onset of symptoms. This paper explores the application of the “Yang transforming into Qi and Yin forming shape” theory from the “Huangdi Neijing” in the diagnosis and treatment of AR. Research indicates that Yang deficiency is the root cause of AR, while excessive Yin formation represents the manifestation of the disease. The main treatment principle is to warm and unblock Yang, supplemented by the expulsion of Yin pathogens, providing a new theoretical basis and treatment strategy for the TCM management of AR. This approach holds promise for offering safer and more effective treatment options for patients.